Data from: Nowhere to hide: the impact of linear disturbances on the spatial dynamics of predator and prey in a large mammal system - DeMars, Craig; Boutin, Stan (Zenodo, 2020)
Rapid landscape alteration associated with human activity is currently challenging the evolved dynamical stability of many predator-prey systems by forcing species to behaviorally respond to novel environmental stimuli. In many forested systems, linear features (LFs) such as roads, pipelines and resource exploration lines (i.e. seismic lines) are a ubiquitous form of landscape alteration that have been implicated in altering predator-prey dynamics. One hypothesized effect is that LFs facilitate predator movement into and within prey refugia, thereby increasing predator-prey spatial overlap. We evaluated this hypothesis in a large mammal system, focusing on the interactions between boreal woodland caribou (Rangifer tarandus caribou) and their two main predators, wolves (Canis lupus) and black bears (Ursus americanus), during the calving season of caribou. In this system, LFs extend into and occur within peatlands (i.e. bogs and nutrient-poor fens), a habitat type highly used by caribou due to its refugia effects. Using resource selection analyses, we found that LFs increased predator selection of peatlands. Female caribou appeared to respond by avoiding LFs and areas with high LF density. However, in our study area most caribou cannot completely avoid exposure to LFs and variation in female response had demographic effects. In particular, increasing proportional use of LFs by females negatively impacted survival of their neonate calves. Collectively, these results demonstrate how LFs can reduce the efficacy of prey refugia. Mitigating such effects will require limiting or restoring LFs within prey refugia, though the effectiveness of mitigation efforts will depend upon spatial scale, which in turn will be influenced by the life history traits of predator and prey. Caribou GPS Location Data csv file containing GPS location data of boreal caribou. Note that data has been cleaned as per the methods outlined in the Journal of Animal ecology paper. AllCaribouDataSpatialOverlapAnalysis.csv Wolf GPS Location Data csv ...